The Reality of Applied the Global Entrepreneurial In Jordanian Universities - Al-Ajami, Mohammed Saleh (Journal of Educational and Psychological Sciences, 2023)
The study aimed at finding out the reality of applied the global entrepreneurial in Jordanian universities, and to achieve the goal of the study questionnaire was developed Consisting of (31) paragraph were confirmed validity and reliability, the study sample consisting of (150) Leader, the study results showed that the degree of appreciation and the reality of applied the global entrepreneurial in Jordanian universities from the standpoint of the study sample was a high degree, the lack of significant differences in the study sample to the reality of applied the global entrepreneurial in Jordanian universities, due to the job title and Years of Experience at the macro level of the instrument differences. In the light of these results, the study recommended the necessity of to enhance the concept of global leadership in universities by increasing interest in applying global leadership in these universities, which contributes to enhancing their competitiveness at the local and international levels.